Assessing the Role of Water Users Associations in Operating and Maintaining the Improved Irrigation System in Egypt - F. Elhadad; T. Elgamal; A. Mady (Arab Universities Journal of Agricultural Sciences, 2020)
The current study investigated the influence of Water Users Associations (WUAs) in the operation and the maintenance of the facilities of improved areas in Egypt. With the establishment of irrigation improvement projects, it was planned that WUAs would play an important role in improving water management and ensuring the sustainability of the improved system through enhancing the cooperation between farmers, scheduling the irrigation and maintaining the improved Mesqas (distributaries). The current study aims to check the actual situation after the implementation of irrigation improvement projects through collecting data from samples according to design questionnaires in the improved areas, and analyzing the collected data to investigate the influence of these associations. The results showed that the influence of WUAs in Egypt was still very limited. Irrigation practices were close to the old trend, which was targeting by irrigation improvement projects. The improved system was operated based on the natural relationships between farmers, with no predefined irrigation schedule targeting improving water management. The operator was the main person, and his role was just to arrange the irrigation based on the reservation of the farmers. Old lifting points were still used in the new system. This gave the farmers the chance to work individually, which could decrease the direct conflicts between them, but it had negative impact on water use efficiency. The maintenance of the system was poor, and the target was just to make the system work without considering the sustainability of the system. The study discussed the reasons behind the weak influence of WUAs including the characteristics of such organizations and different factors that affect their performance. In addition, the study suggested the required steps to improve the capacities of these organizations and to enhance the coordination between farmers including the precise distribution of water supply, and the support from the government.